Mössbauer cell for low-temperature studies of catalysts under reaction conditions - Perez de Berti, Ignacio Omar (2015)
Mössbauer spectroscopy is an essential tool to investigate the structure of Fe supported catalysts and their changes, when they are used in the Fischer-Tropsch synthesis. A cell, that allows keeping the samples in the same atmosphere of the reduction treatment, was designed in order to characterize the Fe species without changing the working atmosphere avoiding the oxidation. It allows to measure at low temperatures in a helium closed-cycle refrigerator. Besides, this cell is useful to perform Mössbauer measurements on the used catalysts, preserving the oxidation of its species, using an inert atmosphere. In this work, we describe the details of this new cell and, as an example of its utility, we present the results obtained with a system of 12 nm iron oxide nanoparticles supported on a mesoporous silica matrix.